KETIDAKSANTUNAN KESEMBRONOAN DAN MELECEHKAN MUKA PADA TUTURAN ANTARPEMAIN GAME ROBLOX - Mayang Novia Fitriani; Hera Meganova Lyra; Asri Soraya Afsari (STKIP Subang, 2026)
Interactions among online gamers are increasingly dominated by language that violates norms of politeness, particularly on the Roblox platform, which offers a voice chat feature. This phenomenon forms the basis of this study, which analyzes forms of linguistic impoliteness in the game Kite Combat on the Roblox platform. This study aims to describe the categories and subcategories of linguistic impoliteness used in player-to-player discourse based on the theory by Rahardi et al. The approach used in this study is qualitative descriptive, employing the Free Listening and Speaking (SLBC) technique, along with recording and note-taking for data collection. Player-to-player discourse in the Kite Combat game serves as the subject of this study. The findings revealed a total of 35 instances of linguistic impoliteness, comprising 30 instances of the frivolous impoliteness category and 5 instances of the face-aggravating impoliteness category. The privolous impoliteness category was dominated by the subcategory of boasting in jest. Meanwhile, the face-aggravating category consided of criticizing through cynicism, insulting through ridicule, and swearing with offensive language. These findings indicate that frivolous impoliteness is more frequently employed in player interactions than face-aggravating impoliteness.